PENGARUH CAPITAL ADEQUACY RATIO, NON-PERFORMING FINANCING, DAN FINANCING TO DEPOSIT RATIO TERHADAP VULNERABILITY BANK UMUM SYARIAH DI INDONESIA TAHUN 2020–2024 - Rafiustha Adi Kusuma; Muhammad Iqbal; Andika Saputra (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on the vulnerability of Sharia commercial banks in Indonesia for the period 2020-2024. The main problem studied is the extent to which internal banking factors, especially capital, financing risk, and liquidity, affect the level of vulnerability (vulnerability) of the Islamic banking system as measured using the Z-score approach. This research occupies an important position in filling the gap of empirical studies on the financial stability of Islamic banking through a quantitative approach based on pooled time series (Pooled OLS) data using EViews 13 software. The method used is a quantitative approach with regression analysis techniques pooled time series data (pooled OLS) using software EViews 13. The results showed that CAR and NPF had a positive but not significant effect on vulnerability, while FDR had a negative and significant effect. Simultaneously, the three variables significantly affect the vulnerability of Islamic banks. This result confirms that the stability of Islamic banking is influenced by a combination of capital strength, financing quality, and intermediation efficiency in maintaining financial resilience in accordance with Islamic economic principles.  Keywords : Capital Adequacy Ratio, Non-Performing Financing, Financing to Deposit Ratio, Vulnerability, Islamic Banking